Self‐Delivered Supramolecular Nanomedicine with Transformable Shape for Ferrocene‐Amplified Photodynamic Therapy of Breast Cancer and Bone Metastases. (26th July 2021) - Qin, Yi; Tong, Fan; Zhang, Wei; Zhou, Yang; He, Siqin; Xie, Rou; Lei, Ting; Wang, Yushan; Peng, Shaojun; Li, Zhaofeng; Leong, Julian; Gao, Huile; et al.
Abstract: Although nanomedicines can passively target tumor through the enhanced permeability and retention (EPR) effect, their distribution and retention are limited by complex tumor microenvironment. Herein, a self‐delivery supramolecular nanoplatform with shape‐transforming capacity (Ce6‐CD/Fc‐pep‐PEG) is constructed by the host‐guest interaction between chlorin e6‐ conjugated β‐cyclodextrin (Ce6‐CD) and ferrocene‐modified FFVLG3 C‐PEG conjugates (Fc‐pep‐PEG). Following passive accumulation mediated by the EPR effect, hydrophobic Fc is oxidized to water‐soluble Fc + by endogenous ROS in tumor sites. The resulting Fc + ‐pep‐PEG fragment dissociated from Ce6‐CD and recombined to nanofibers through the intermolecular hydrogen bonds among FFVLG3 C peptide chains, thus enhancing the retention. Meanwhile, the Ce6‐CD fragment still maintained the form of spherical micelles with a relatively smaller size to penetrate into the deep tumor regions. Moreover, the cascade Fenton reaction catalyzed by Fc generated OH and O2 to relieve hypoxia and amplify PDT efficiency. In turn, ROS generated by PDT promoted shape‐transformation and continuous occurrence of Fenton reaction. In vitro and in vivo evaluations verify that through the positive feedback loop, Ce6‐CD/Fc‐pep‐PEG can induce a potent antitumor immune response and achieve ROS‐potentiated elimination of primary tumor and bone metastasis. Abstract : A self‐delivery supramolecular nanoplatform (Ce6‐CD/Fc‐pep‐PEG) is constructed to co‐deliver ferrocene and chlorin e6 for self‐amplified chemo‐photodynamic therapy of breast cancer and bone metastases. Its shape‐transforming capacity further improves the penetration and retention of Ce6‐CD/Fc‐pep‐PEG in the tumor, which enhances the therapy efficiency and is enlarged by the ROS generated by photodynamic therapy.